Change and diversity in smallholder rice-fish systems: Recent evidence from Bangladesh - Dey, Madan M.; Spielman, David J.; Haque, A.B.M. Mahfuzul; Rahman, Md. Saidur; Valmonte-Santos, Rowena (International Food Policy Research Institute, 2012)
Efforts to unlock the genetic potential of both rice and fish, when combined with efforts to improve the management of rice–fish systems, have considerable proven potential for increasing agricultural productivity and food security. In Bangladesh, estimates suggest that the country’s potential rice–fish production system encompasses between two and three million hectares of land. Despite three decades of research on biophysical and technical aspects of rice–fish systems, this potential has not been realized fully due to insufficient attention given to the social, economic, and policy dimensions of system improvement. This paper provides a characterization of the diverse and changing nature of rice–fish systems in Bangladesh by combining data from a novel upazilla-level (sub-district-level) survey of fishery officers with household surveys, focus group discussions, and a meta-review of the literature on aquaculture in the country. The resulting analysis sheds new light on the economic viability of different rice–fish systems and recommends policy and investment options to further improve the development and delivery of rice–fish technologies. Findings indicate that in addition to concurrent rice–fish systems, alternating rice–fish systems and collectively managed systems offer considerable potential for increasing productivity and farm incomes in Bangladesh. Findings also suggest that although the emergent innovation system around these rice–fish systems is fairly dynamic, there is a need for more supportive policies and investments—and analysis of the intended and unintended impacts of these policies and investments.